Compound Wumei Powder Inhibits the Invasion and Metastasis of Gastric Cancer via Cox-2/PGE2-PI3K/AKT/GSK3β/β-Catenin Signaling Pathway - Ma, Nai-Xia (Evid Based Complement Alternat Med, 2017)
To explore the role of CWP in invasion and migration of gastric cancer cells and its underlying molecular mechanism, we performed the experiment in SGC-7901 cells both in vitro and in vivo. In the cell experiment, we evaluated cell proliferation by MTT assay. The results showed that CWP can inhibit the growth of SGC-7901 cells. The influence on cell migration and invasion was detected by wound-healing and Transwell invasion assays. The results showed that the abilities of invasion and migration are restrained in CWP group. Western blot showed that CWP can decrease the expression of Cox-2 and inhibit the PI3K/AKT/GSK3β/β-catenin signaling pathway. In the animal experiment, we observed that CWP had an inhibitory effect on the growth of xenograft tumors of nude mice. IHC assay, ELISA, RT-PCR assay, and Western blot assay were used to test relevant cytokines of Cox-2/PGE2-PI3K/AKT/GSK3β/β-catenin pathway. The results showed that CWP can suppress relevant cytokines of Cox-2/PGE2-PI3K/AKT/GSK3β/β-catenin pathway. In conclusion, we suggest that CWP inhibits the invasion and metastasis of SGC-7901 cells via Cox-2/PGE2-PI3K/AKT/GSK3β/β-catenin signaling pathway.